1991
DOI: 10.3109/00016489109137410
|View full text |Cite
|
Sign up to set email alerts
|

Trauma of the Cricoid and Interlocked Stress

Abstract: In young rabbits the effects were studied of an anterior midline and a bilateral split with and without traumatisation of the perichondrium and subperichondrial cartilage on the inner side of the ring. Various interventions produced specific patterns of distortions. It is concluded that release of interlocked stress in the cartilage is of paramount importance for the development of deformities. A specific feature of the circular cartilaginous structure seems to be that the tensile forces on the outer side of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…These canals are mineralized, and then undergo a process of endochondral ossification. 24 Figure 1 shows picosirius red staining of thyroid cartilage sections from a young adult male. Picosirius red staining detects collagen I and III and may be birefringent into green/yellow areas depending on fiber thickness.…”
Section: Gross Structure and Biomechanics Of Laryngotracheal Cartilagesmentioning
confidence: 99%
“…These canals are mineralized, and then undergo a process of endochondral ossification. 24 Figure 1 shows picosirius red staining of thyroid cartilage sections from a young adult male. Picosirius red staining detects collagen I and III and may be birefringent into green/yellow areas depending on fiber thickness.…”
Section: Gross Structure and Biomechanics Of Laryngotracheal Cartilagesmentioning
confidence: 99%
“…Ciagli, when developing his PDT technique, at first argued the safety of subcricoid tracheostomy 2 but later acknowledged that puncture between the first and second tracheal arches was preferable 3 . (Figure 3) suprastomal granulation ventricular mucosa 22 , (Figure 1) ( Figure 4 24 . Van Heurn et al 21 studied the trachea in autopsy specimens after PDT and found that two patients with subcricoid cannulation suffered fracture of the cricoid.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive distortion of an intact cricoid ring has been previously reported to develop after an endolaryngeal injury in the young rabbit [4,11]. The injury resulted in a circular scar considered to be responsible for partial collapse of the cricoid.…”
Section: Immediate and Long-term Distortion Of The Split Cricoid Aftementioning
confidence: 94%
“…Hardly any clinical data are available on the later growth of a distorted cricoid. Animal experiments have demonstrated specific cricoid anomalies to develop after various types of splits and other lesions [3][4][5]. In vivo the cricoid is suspended in a symmetrical complex of muscles, membranes and ligaments.…”
Section: Introductionmentioning
confidence: 98%